The Influence of Green Intellectual Capital on Sustainable Competitive Advantage with Green Innovation as a Mediator in Pematangsiantar City - Sisca; Pasaman Silaban; Fajar Rezeki Ananda Lubis (International Journal of Computational and Experimental Science and Engineering, 2025)
This study aims to see how much influence green intellectual capital contributes to increasing competitive advantage with green innovation as a mediator in Pematangsiantar City. This research method uses a mixed approach. Data collection using research instruments and statistical data analysis. The population is all MSMEs engaged in the food and beverage industry sector in Pematangsiantar City. The number of samples in this study was 300 samples. The measurement scale in this study is a Likert scale gradation from the lowest to the highest. Descriptive statistical analysis is used to determine the description of the characteristics of respondents and the answers of research respondents. Testing the estimation and hypothesis of the research model using the Partial Least Square Structural Equation Model (PLS-SEM) method. The results of the study show that Green human capital, structural capital, and Green relational capital have a significant effect on green innovation in MSMEs in Pematangsiantar City. Likewise, Green human capital, Green structural capital, and Green relational capital have a significant effect on sustainable competitive advantage in MSMEs in Pematangsiantar City. Furthermore, Green innovation has a significant effect on sustainable competitive advantage in MSMEs in Pematangsiantar City. Green innovation is able to mediate the influence between green human capital, green structural capital and green relational capital on sustainable competitive advantage in MSMEs in Pematangsiantar City.